Multiple dental gemination: a clinical case report - Hernández, Jesús Alberto; Villavicencio, Judy Elena; Moreno, Freddy (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Dental gemination and fused teeth are anomalies affecting in shape and number the normal dental formula, interfering with the development of the dentition and occlusion of the growing patient. Gemination is more frequent in anterior teeth with a prevalence of 0.5% in the primary dentition and 0.1% in the permanent dentition. We present the case of an 8 year old child, with incomplete bilateral gemination of the maxillary central incisors. Additionally, in this paper we outline the surgical treatment for separating the teeth and the treatment performed for the correction of the existing malocclusion. It is important to notice that geminated teeth do not share cameral and radicular pulp; therefore it was not necessary to perform root canal therapy.